Implementing the Project-based Learning Model Through Two-dimensional Art-making To Improve Elementary School Students' Critical Thinking Skills - Alfian Eko Widodo Adi Prasetyo; Andhika Yahya Putra (Universitas Wahid Hasyim Semarang, 2026)
This study was motivated by the low level of elementary school students' critical thinking skills, particularly in expressing criticism and opinions. A Project-Based Learning (PjBL) model was needed to actively involve students in critical thinking activities. The purpose of this study was to describe the implementation of PjBL through the creation of two-dimensional artworks as a learning activity that helps students achieve the indicators of critical thinking. This study employed an Action Research (AR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The participants were 25 fifth-grade elementary school students. Data were collected through observation, interviews, and documentation, while the data were analyzed using descriptive quantitative techniques with percentage-based achievement indicators. The findings show that the use of PjBL improved students' critical thinking skills. In Cycle I, learning was carried out through the creation of two-dimensional artworks that presented environmental issues and were followed by group presentations. In Cycle II, the activity was strengthened through two-dimensional art-making and a mini-exhibition. The observation results showed an increase in students' critical thinking performance from 71% in Cycle I to 90% in Cycle II. All four indicators showed meaningful improvement, although one indicator still required further strengthening. These findings indicate that PjBL is effective in improving students' critical thinking skills.